Performance characteristics of collapsible CaO-SiO2 based ceramic core material via layered extrusion forming. Issue 6 (15th April 2019) - Yang, Li; Tang, Shiyan; Li, Guanjin; Liu, Fuchu; Liu, Xinwang; Jiang, Wenming; Fan, Zitian
Abstract: An additive manufacturing method, named layered extrusion forming (LEF), was adopted to fabricate collapsible ceramic cores. Green samples were first fabricated using CaCO3 and SiO2 powders as precursor materials and aqueous polyethylene glycol solution-silica sol as a composite binder and then calcined at 1100 °C − 1300 °C for 2 h. The effect of CaO-SiO2 molar (C/S) ratio on the performance characteristics of green and sintered samples was investigated. The results showed that the slurries exhibited a pseudoplastic behavior for different C/S ratios, and the linear shrinkage of the green samples showed a slight increase with decreasing C/S ratio. After sintering, the reduction of C/S ratio obviously decreased linear shrinkage and bending strength, whereas strengthened the hydration resistance. The microstructure analysis demonstrated that the porosity was increased with decreasing C/S ratio, thereby weakening the bending strength. The ceramic cores samples were constituted by Ca2 SiO4 and CaO phases. The existence of the Ca2 SiO4 improved the hydration resistance, leading to relative lower collapsibility. The sintered samples with a C/S ratio of 2.45 obtained a superior collapsibility in water, especially in the higher water temperature, which is significant for industry applications.